2019
DOI: 10.1088/1757-899x/687/2/022034
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of high alumina cement based on metallurgy wastes

Abstract: In this paper efficient types of binders – high alumina cements are considered. The shortage of industrial alumina and its high cost constrain the development of high-aluminate cements production. Waste from a number of metallurgical industries can be used as raw materials for their production. The aim of the investigation was to study the influence of metallurgical waste on the mineral formation of aluminate clinker and the properties of cement based on it. As a replacement of industrial alumina, dust of gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…To study the possibility of using aluminous cement of the GTs40 and GTs50 grades of a Russian manufacturer, there was conducted a research of briquettes, which are mineral wool and non-fibrous inclusions. Briquettes were exposed to thermal and humidity treatment binder together with waste of mineral wool production [6].…”
Section: Discussionmentioning
confidence: 99%
“…To study the possibility of using aluminous cement of the GTs40 and GTs50 grades of a Russian manufacturer, there was conducted a research of briquettes, which are mineral wool and non-fibrous inclusions. Briquettes were exposed to thermal and humidity treatment binder together with waste of mineral wool production [6].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other wastes have been used in the production of alumina cement by Krivoborodovet al 20 , as a source of alumina, such as the slag of ferroalloys manufacture and the dust of gas cleaning plants of aluminum electrolysis. The study has indicated an improvement in the properties of alumina cement related to the slag from ferrovanadium production which contains 67.4 wt% of Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Ordinarily, calcium aluminate phases in the largescale production of aluminous cements are synthesized by high-temperature alloying or sintering using raw materials that contain Al 2 O 3 and СаO and some amount of impurities as well [7,9,26,27]. The major impurities are silica and iron, magnesium, titanium, and alkali oxides.…”
Section: Introductionmentioning
confidence: 99%